1999
DOI: 10.7600/jspfsm1949.48.493
|View full text |Cite
|
Sign up to set email alerts
|

Examining Reproducibility of Force-Exertion Pattern and Reliability of Force-Time Parameters in the Development Phase During Static Explosive Grip Exertion

Abstract: The evaluation of muscular power function has been mainly limited to dynamic contraction, but

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Until now, attention has been paid to only MGS in general grip strength exerted by isometric contraction, but Demura et al (4) tried to evaluate muscle power by force-time parameters exerted during explosive isometric gripping. They report that the ICC of the maximal grip value was more than 0.9, but the ICC of the force-time parameters was lower than 0.7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, attention has been paid to only MGS in general grip strength exerted by isometric contraction, but Demura et al (4) tried to evaluate muscle power by force-time parameters exerted during explosive isometric gripping. They report that the ICC of the maximal grip value was more than 0.9, but the ICC of the force-time parameters was lower than 0.7.…”
Section: Discussionmentioning
confidence: 99%
“…Demura et al (4) tried to evaluate muscle power by force-time parameters exerted during explosive isometric gripping. They reported that the interclass correlation coefficient (ICC) of the maximal grip value was more than 0.9, but the ICC of the force-time parameters was lower than 0.7.…”
mentioning
confidence: 99%
“…The larger grip strength was selected as a representative value. The measurement of the explosive hand grip exertion was performed using methods based on the report of Demura et al (1999). After a signal, the subjects exerted explosive hand grip in the same posture as when measuring maximal strength, and after 5 seconds the signal to cease was sounded.…”
Section: Measurement Of the Hand And Toe Grip Exertionsmentioning
confidence: 99%
“…Until now, studies on handgrip have been mainly performed by using the dominant hand (Demura et al, 1999;Nakada & Demura, 2013;Nakada et al, 2005;Yamaji et al, 2002;Yamaji et al, 2000). Meanwhile, a previous study examined the toes during bipedal walking (Hughes et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation